Trematode Diplostomum pseudospathaceum inducing differential immune gene expression in sexual and gynogenetic gibel carp (Carassius gibelio): parasites facilitating the coexistence of two reproductive forms of the invasive species - Fuad, Md Mehedi Hasan; Tichopád, Tomáš; Ondračková, Markéta; Civáňová Křížová, Kristína; Seifertová, Mária; Voříšková, Kristýna; Demko, Martin; Vetešník, Lukáš; Šimková, Andrea (Frontiers in Immunology, 2024)
Parasite-mediated selection is considered one of the potential mechanisms contributing to the coexistence of asexual-sexual complexes. Gibel carp (Carassius gibelio), an invasive fish species in Europe, often forms populations composed of gynogenetic and sexual specimens. In the present study, experimental infection was induced in gynogenetic and sexual gibel carp using eye-fluke Diplostomum pseudospathaceum (Trematoda), and the transcriptome profile of the spleen as a major immune organ in fish was analyzed to reveal the differentially expressed immunity-associated genes related to D. pseudospathaceum infection differing between gynogenetic and sexual gibel carp. High parasite infection was found in gynogenetic fish when compared to genetically diverse sexuals. Although metacercariae of D. pseudospathaceum are situated in an immune-privileged organ, our results show that eye trematodes may induce a host immune response. We found differential gene expression induced by eye-fluke infection, with various impacts on gynogenetic and sexual hosts, documenting for the majority of DEGs upregulation in sexuals, and downregulation in asexuals. Differences in gene regulation between gynogenetic and sexual gibel carp were evidenced in many immunity-associated genes. GO analyses revealed the importance of genes assigned to the GO terms: immune function, the Notch signaling pathway, MAP kinase tyrosine/threonine/phosphatase activity, and chemokine receptor activity. KEGG analyses revealed the importance of the genes involved in 12 immunity-associated pathways – specifically, FoxO signaling, adipocytokine signaling, TGF-beta signaling, apoptosis, Notch signaling, C-type lectin receptor signaling, efferocytosis, intestinal immune network for IgA production, insulin signaling, virion - human immunodeficiency virus, Toll-like receptor signaling, and phosphatidylinositol signaling system. Our study indicates the limited potential of asexual fish to cope with higher parasite infection (likely a loss of capacity to induce an effective immune response) and highlights the important role of molecular mechanisms associated with immunity for the coexistence of gynogenetic and sexual gibel carp, potentially contributing to its invasiveness.